Innovation and maritime transport: A systematic review. Issue 3 (September 2020) - Koukaki, Theodora; Tei, Alessio
Highlights: Maritime innovation studies normally focus on just the implementation process. Industry has a leading role in promoting innovation studies. Academic research in often pushed by industrial advancements to study innovation. Academic studies are quite scattered, often focusing on case studies. Difficulties to generalise research outcomes. Abstract: Innovation is often defined as the introduction of a new concept aiming at improving a certain situation, either using new solutions or a novel combination of already existing resources. In the shipping industry, innovation is a determining factor of shipping evolution and company success. Despite the important role that innovation plays for the shipping industry, academic research is quite fragmented as it usually focuses on specific cases with few attempts for generalisation. Thus, despite a growing interest from scholars, the shipping industry is still often defined as conservative and it is often not easy to highlight innovative trends and common methodologies to investigate innovation in the maritime sector. The current study applies a systematic review approach in order to discuss main trends in current innovation studies as well as for understanding if published researches are aligned with the industry plans. The research finds out that industry is often leading the research agenda while scholars are often more focused in discussing the innovation implementation phase rather than looking for novel applications or developments.